2003
DOI: 10.1089/105072503321319468
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Action on Skin: Diverging Effects of Topical versus Intraperitoneal Administration

Abstract: Previously, we demonstrated stimulation of epidermal proliferation and hair growth in triiodothyronine (T(3)) treated mice. To distinguish skin effects of directly applied T(3) from those of systemic hyperthyroidism, we treated CD-1 mice with either intraperitoneally (IP) or topically administered T(3). Relative to controls, mice receiving T(3) IP had 10% thinner epidermis (p < 0.01) and 48% fewer hairs (p < 0.001). By contrast, mice receiving T(3) topically had 78% thicker epidermis (p < 0.01) and 160% more h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 22 publications
2
51
1
2
Order By: Relevance
“…The function of THs in controlling the balance between cell proliferation and cell differentiation in the skin has proven to be puzzling. In fact, reports have indicated that they are essential for optimal epidermal cell proliferation (Safer et al, 2003;Safer, 2005). In vitro, T3 stimulates keratinocyte proliferation.…”
Section: Function Of Ths In Development and Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…The function of THs in controlling the balance between cell proliferation and cell differentiation in the skin has proven to be puzzling. In fact, reports have indicated that they are essential for optimal epidermal cell proliferation (Safer et al, 2003;Safer, 2005). In vitro, T3 stimulates keratinocyte proliferation.…”
Section: Function Of Ths In Development and Homeostasismentioning
confidence: 99%
“…In vitro, T3 stimulates keratinocyte proliferation. In vivo, topical T3 stimulates epidermal proliferation, dermal thickening and hair growth (Safer et al, 2001;Safer et al, 2003;Safer, 2005). Topical triac (tri-iodothyroacetic acid) thickens skin by stimulating the production of collagen (Faergemann et al, 2002;Yazdanparast et al, 2004).…”
Section: Function Of Ths In Development and Homeostasismentioning
confidence: 99%
“…Thyroid hormone is an important regulator of epidermal homeostasis. In tissue culture studies using surrogates for DNA expression, T 3 has been shown to stimulate growth of both epidermal keratinocytes and dermal fibroblastes [3,4]. In addition, thyroid hormone appears to be necessary for both the initiation and maintenance of hair growth and normal secretion of sebum.…”
Section: Introductionmentioning
confidence: 99%
“…First, hypothyroidism is associated with retarded wound repair probably through decreasing collagen synthesis and or keratinocyte proliferation [21,23,24] which is reversible with thyroid hormone replacement [21,25]. Second, in vitro and in vivo studies have designated that thyroid hormones stimulate keratinocyte and epidermal proliferation as well as hair growth [20,21,26]. Finally, it has been shown that daily treatment with 150 ng topical T3 in mice improves wound closure significantly [19].…”
Section: Discussionmentioning
confidence: 99%
“…T4 is converted by intracellular thyroid hormone deiodinases to T3, the active thyroid hormone, T3 [15,16]. Apikoglu-Rabus et al revealed that liothyronine (T3), the active thyroid hormone, accelerate wound healing in mice [17] and it is probably through proliferation of keratinocytes [18][19][20][21]. However, to date, no information about effects of thyroid hormones on diabetic wounds is available.…”
Section: Introductionmentioning
confidence: 99%